Deixis Analysis on Comments of Taylor Swift’s YouTube Channel - Monica Devi Setiawan; Adrallisman, Adrallisman (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2023)
This research entitled Deixis Analysis on Comments of Taylor Swift’s YouTube Channel. The purposes of the research are to find out the types of deixis and interpret the meaning of utterances based on deixis that found on comments in “Back to December” of Taylor Swift’s YouTube channel. The method of this research used descriptive qualitative research. The writer used Levinson’s theory (1983). In this research, the writer analyzed 32 comments on Taylor Swift’s YouTube channel. There are 11 cases of person deixis, place deixis 2 cases, time deixis 1 case, discourse deixis 10 cases, and last but not least, social deixis 8 cases. The writer concludes that the comments are mostly dominated with person deixis which are important in pragmatics study.